High pressure generation in the Kawai-type multianvil apparatus equipped with sintered diamond anvils. Issue 1 (2nd January 2020) - Yamazaki, D.; Ito, E.
ABSTRACT: Generation of high pressure is a key to the investigation of the interior of the Earth. The Kawai-type multianvil apparatus (KMA) has been widely used in the fields of Earth science and material science. In conventional KMA, tungsten carbide (WC) has been used as the second stage anvil material. However, attainable pressure is limited to ∼70 GPa even if newly developed WC is used. Recently, on the other hand, second stage anvils of sintered diamond that is much harder than WC have enabled us to extend the pressure range of KMA up to 120 GPa, corresponding to the pressure of the D" layer in the Earth's mantle. It is evident that our development of pressure generation facilitates the investigation of the structure and dynamics of the deep mantle of the Earth.